Implementing the capability approach in health promotion projects: Recommendations for implementation based on empirical evidence. (December 2022) - Till, Maike; Abu-Omar, Karim; Ferschl, Susanne; Abel, Thomas; Pfeifer, Klaus; Gelius, Peter; ,
Abstract: Objective: The aim of this paper was to develop a framework for the use of the capability approach in health promotion projects, which could guide future projects as well as improve the comparability of the projects' effectiveness. Method: The study involved a three-stage process comprising a total of six steps. We first developed a theoretical model and then analyzed data from four empirical studies that had implemented projects using the capability approach between 2015 and 2018 in the settings of kindergartens, schools, vocational training, and communities to promote an active lifestyle. Finally, we developed a framework for the use of the capability approach in health promotion projects based on the analysis of the data. Results: We developed a theoretical model of the "capability cycle, " which was used for further analysis. There were divergent understandings of the capability approach due to existing theoretical constructs that are commonly used by the scientific teams of the projects. Further, the conceptualization, implementation, and evaluation of the capability approach within the four settings showed discrepancies, which inhibited a comparison of their effectiveness. The developed framework comprises recommendations regarding the planning of a project, its implementation, and especially its evaluation in future comparisons of project effectiveness. Conclusion: This paper provides a comprehensive analysis of four projects for which we developed a framework using a participatory approach. The findings can help research teams in the conceptualization, implementation, and evaluation of future projects that focus on improving capabilities in the field of health promotion. Further, the established framework will help facilitate comparisons of capability-oriented health promotion projects in terms of their effectiveness. Highlights: A Framework to implement the capability approach in health promotion. Developed on experience of four empirical projects. Resources as well as individual and structural factors influence health choices. Capability Approach is in need of a comprehensive evaluation.